An evaluation of the new primary school Turkish language curriculum in practice - Gömleksiz, Mehmet Nuri; Bulut, Ilhami (My University, 2007)
The aim of this study is to determine the views of classroom teachers about the effectiveness of the new primary school Turkish language curriculum in practice. For that aim, a 33-item Likert-type Turkish Language Curriculum Scale was developed. The population includes 784 classroom teachers working in 64 pilot schools in İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay, Samsun and Bolu cities. The data were analyzed in terms of city, classroom, gender, teaching experience, education level and student number variables. Independent samples t test, Kruskal Wallis H test, variance analysis, Mann Whitney U, Scheffe and LSD tests were used to analyze the data. Statistically significant differences were found among the views of the teachers in terms of city, classroom and gender variables. The learning attainments, content and teaching-learning activities in the new Turkish language curriculum were found effective by the teachers. But the evaluation part of the new curriculum was not found effective in practice. With the study, the teachers are suggested to have systematic and effective in-service seminars to learn and use the evaluation techniques aimed at the new primary school Turkish language curriculum.
Yeni ögretim türkçe dersi ö?retim programinn uygulamadaki etkili?inin de?erlendirilmesi
Keywords: Constructivism; New primary school Turkish language curriculum; Turkish language education